2008
DOI: 10.1017/s0007114508035940
|View full text |Cite
|
Sign up to set email alerts
|

Precocious gut maturation and immune cell expansion by single dose feeding the lectin phytohaemagglutinin to suckling rats

Abstract: The dietary lectin phytohaemagglutinin (PHA) induces gut growth and precocious maturation in suckling rats after mucosal binding. The present study investigated the dose range in which PHA provokes gut maturation and if it coincided with immune activation. Suckling rats, aged 14 d, were orogastrically fed a single increasing dose of PHA: 0 (control), 2, 10, 50 or 250 mg/g body weight (BW) in saline. The effect on gut, lymphoid organs and appearance of CD3 þ (T-lymphocyte) and CD19 þ (B-lymphocyte) cells in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Several changes were observed during the study, among others in haematology and blood biochemistry, as compared with controls, however, it should be emphasized that all results, including the results obtained in the group treated with the high dose of kidney bean lectin, were within the physiological range for piglets. Nevertheless, it is known that lectins from legumes, including kidney bean lectins, may provoke immune system development (Prykhod'ko et al, 2009). Plant lectins may increase allergic reactions in humans and animals (Cordain et al, 2000;Lavelle et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several changes were observed during the study, among others in haematology and blood biochemistry, as compared with controls, however, it should be emphasized that all results, including the results obtained in the group treated with the high dose of kidney bean lectin, were within the physiological range for piglets. Nevertheless, it is known that lectins from legumes, including kidney bean lectins, may provoke immune system development (Prykhod'ko et al, 2009). Plant lectins may increase allergic reactions in humans and animals (Cordain et al, 2000;Lavelle et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney bean lectin, a carbohydrate-binding protein, is constituted by a mixture of isoforms, PHA-E 4 , PHA-E 3 L, PHA-E 2 L 2 , PHA-EL 3 , PHA-L 4 , originally characterized by erythro-and leuco-agglutinating activity (Nordman et al, 1964;Leavitt et al, 1977). After gastric gavage it manifested strong promitotic activity in gut mucosa, and stimulated immune and endocrine systems in suckling piglets -described jointly as precocious maturation (Rådberg et al, 2001;Thomsson et al, 2007;Prykhod'ko et al, 2009). Importantly, maturation effects in the gastrointestinal tract were induced without systemic absorption of lectin (Linderoth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, single or few oral inoculations of PHA to suckling rats and piglets induced structural and functional maturation of the gut evidenced as a decreased villi height, increased proliferation and crypt depth and a shift in the expression of enterocytes disaccharidases to an adult-type characterized by a decreased lactase and increased sucrase and maltase activities. In consequence, PHA has been proposed as an inductor of precocious maturation of the gut in order to better prepare the farm animals to digest and absorb the post weaning feed, as well as a treatment of mammals having an immature intestine and a therapy for individuals with a defective growth of the mucosa during total parenteral nutrition (Fitzgerald et al, 2001;Linderoth et al, 2005Linderoth et al, , 2006Prykhod'ko, Fed'kiv, Linderoth, Pierzynowski, & Westrom, 2009;Radberg et al, 2001;Thomsson, Rantzer, Westrom, Pierzynowski, & Svendsen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that gut maturation can be induced precociously in suckling rats by enteral provocation with phytohaemagglutinin (PHA) - a lectin[ 15 , 16 ], or proteases[ 17 ], mimicking the naturally occuring processes at weaning. Furthermore, provocation with PHA had effects on the thymus and the recruitment of CD3 + T-lymphocytes to the gut mucosa[ 16 ]. In fact, it has been suggested that natural GI development at weaning is dependent on T-cell activation in rats[ 18 ].…”
Section: Introductionmentioning
confidence: 99%